WRITTEN CORRECTIVE FEEDBACK APPLIED BY ENGLISH TEACHER AT THE EIGHTH GRADE STUDENTS OF SMP NU PALANGKA RAYA - Umratul Janah; Wahyuningsih Usadiati; Ristati Ristati (Intensive Journal, 2021)
This study was aimed at investigating written corrective feedback applied by an English teacher in writing class at eighth grade students of SMP NU Palangka Raya. Two research questions were formulated in this study. (1) How is the teacher written corrective feedback technique applied in English class of SMP NU Palangka Raya; (2) What are written feedback patterns applied by an English teacher in writing class at eighth grade students of SMP NU Palangka Raya.  This study was case study with qualitative approach. For the data collection, it was used the instruments such as observation equipped with observation checklist, interview equipped with interview guideline, documentation and field notes. To analyze the data, it was through the techniques: data collection, data display, data reduction, and conclusion/drawing. For the data endorsement, it was used triangulation technique. The results showed that the teacher applied written corrective feedback technique in the class by some steps. The written corrective feedback applied by the teacher focuses on correct word choice, punctuation, grammar, organization, spelling, and content. The teacher also used affective feedback which feedback in the form of motivation on teacher’s writing. The patterns of written corrective feedback were feedback sandwich and gold star. Students’ response through written corrective feedback applied were: (1) teacher written feedback was objective, (2) teacher written feedback was clear, (3) teacher written feedback assisted the students (4) teacher written feedback was encouraging